Excess cancer prevalence in men with HIV: A nationwide analysis of Medicaid data. Issue 10 (14th March 2022) - Koroukian, Siran M.; Zhou, Guangjin; Navale, Suparna M.; Schiltz, Nicholas K.; Kim, Uriel; Rose, Johnie; Cooper, Gregory S.; Moore, Scott Emory; Mintz, Laura J.; Avery, Ann K.; Mukherjee, Sudipto; Markt, Sarah C.
Abstract : Background: Cancer is one of the most common comorbidities in men living with HIV (MLWH). However, little is known about the MLWH subgroups with the highest cancer burden to which cancer prevention efforts should be targeted. Because Medicaid is the most important source of insurance for MLWH, we evaluated the excess cancer prevalence in MLWH on Medicaid relative to their non‐HIV counterparts. Methods: In this cross‐sectional study using 2012 Medicaid Analytic eXtract data nationwide, we flagged the presence of HIV, 13 types of cancer, symptomatic HIV, and viral coinfections using codes from the International Classification of Diseases, Ninth Revision, Clinical Modification . The study population included individuals administratively noted to be of male sex (men), aged 18 to 64 years, with (n = 82, 495) or without (n = 7, 302, 523) HIV. We developed log‐binomial models with cancer as the outcome stratified by symptomatic status, age, and race/ethnicity. Results: Cancer prevalence was higher in MLWH than in men without HIV (adjusted prevalence ratio [APR], 1.84; 95% confidence interval [CI], 1.78‐1.90) and was higher among those with symptomatic HIV (APR, 2.74; 95% CI, 2.52‐2.97) than among those with asymptomatic HIV (APR, 1.73; 95% CI, 1.67‐1.79). The highest APRs were observed for anal cancer in younger men, both in the symptomatic and asymptomatic groups: APR, 312.97; 95% CI, 210.27‐465.84, and APR, 482.26; 95% CI, 390.67‐595.32, respectively. In race/ethnicity strata, the highest APRs were among Hispanic men for anal cancer (APR, 198.53; 95% CI, 144.54‐272.68) and for lymphoma (APR, 9.10; 95% CI, 7.80‐10.63). Conclusions: Given the Medicaid program's role in insuring MLWH, the current findings highlight the importance of the program's efforts to promote healthy behaviors and vaccination against human papillomavirus in all children and adolescents and to provide individualized cancer screening for MLWH. Abstract : The burden of cancer in men living with HIV (MLWH) on Medicaid is substantial. Given the role of the Medicaid program in insuring MLWH, the findings highlight the importance of the program's efforts to promote healthy behaviors and vaccine against human papillomavirus in all children and adolescents and to provide individualized cancer screening for MLWH.